The Frequency of Previously Undiagnosed Diabetes Mellitus in Patients with Acute Coronary Syndrome Using HBALC - Sara Ahmed, Muhammad Zubair, Abdul Salam, Qamar Zaman, Aslam Latif, Amar Deep (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the proportion of previously undiagnosed diabetes mellitus in patients with acute coronary syndrome (ACS) using HbAlc. Methods: A cross-sectional study was conducted at the Department of Cardiology, National Institute of Cardiovascular Diseases Karachi, Pakistan between 15th July, 2020 and 15th January, 2021. One hundred and thirty-nine patients admitted with acute chest pain and diagnosed with ACS were recruited in the study. After a thorough history, clinical examination, ECG, serum troponin-I level, hemoglobin level and HbA1C were done on these patients. Patient’s age, gender, HbAlc level and BMI was noted. Outcome (diabetes, pre-diabetes, non-diabetic) for each patient was noted. Results: Majority of study participants were males (n=98; 70.50%) and the rest were females (n=41; 29.50%). The mean age of study participants was 56.09±4.91 years. The mean±SD HbA1c level in the study population was 5.10%±0.81%. STEMI (n=99; 71.22%) was most common and followed by NSTEMI (n=40; 28.78%). Diabetes Mellitus was diagnosed in 15 (10.79%) study participants. No statistically significant association was found between diabetes mellitus and age, sex, and kind of ACS. Conclusion: Previously undiagnosed diabetes mellitus is quite common in patients with acute coronary syndrome and the physicians should actively look for diabetes mellitus in such patients. Keywords: Diabetes Mellitus, Acute coronary syndrome, STEMI, NSTEMI, HbA1c, Complications, Morbidity.